Determination of iron in cocoa based food product - Bakar, Mohd Izhar Abu (Universiti Sains Malaysia, 2006)
Determination of iron in cocoa based food product The concentrations of iron in the cocoa based products available in local market around Kota Bharu were determined. Out of 15 samples analysed, three were nutritious chocolate drink powder, seven cereal meal product, two chocolate bars, two chocolate flavored beverages and one sample was pure cocoa powder. 1:1 dilution of concentrated nitric acid digestion followed with analysis by flame atomic absorption. The samples were homogenized and were heat to boiling with nitric acid for 30 minutes prior to the analysis. The iron obtained in this study is about 0.6 to 1.0 ppm for powder sample, 0.2 to 0.4 for bar sample and 0.2 ppm for liquid sample. The overall result shows the concentration of iron in the cocoa based food product within the range of 0.2 to 1.3 ppm. v